2018
DOI: 10.1371/journal.pone.0205513
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative optical coherence tomography angiography biomarkers for neovascular age-related macular degeneration in remission

Abstract: PurposeTo characterize quantitative optical coherence tomography angiography (OCT-A) parameters in active neovascular age-related macular degeneration (nAMD) patients under treatment and remission nAMD patients.DesignRetrospective, cross-sectional study.ParticipantsOne hundred and four patients of whom 72 were in Group 1 (active nAMD) and 32 in Group 2 (remission nAMD) based on SD-OCT (Spectral Domain OCT) qualitative morphology.MethodsThis study was conducted at the Centre Ophtalmologique de l’Odeon between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 31 publications
(37 reference statements)
2
40
3
Order By: Relevance
“…Other characteristics used to assess CNV include CNV location, CNV maturity, the presence of core vessels, and the presence of margin loops. 64 Quantitative OCTA parameters, such as BVD, FD, 30 and LAC, 65 have also been used for CNV analysis of AMD. 30 They are useful parameters to evaluate neovascularization activity by assessing the degree of complexity, and vessel nonuniformity of the lesions, respectively.…”
Section: Quantitative Octa Featuresmentioning
confidence: 99%
“…Other characteristics used to assess CNV include CNV location, CNV maturity, the presence of core vessels, and the presence of margin loops. 64 Quantitative OCTA parameters, such as BVD, FD, 30 and LAC, 65 have also been used for CNV analysis of AMD. 30 They are useful parameters to evaluate neovascularization activity by assessing the degree of complexity, and vessel nonuniformity of the lesions, respectively.…”
Section: Quantitative Octa Featuresmentioning
confidence: 99%
“…23 More recently, other studies have studied FD and LAC as potential quantitative biomarkers to characterize CNV branching complexity and heterogeneity, respectively. [11][12][13] FD quantifies the variations in space filling using the box-counting method and provides a way of characterizing branching in terms of complexity. In two-dimensional images, FD attains a value between zero and two with higher values indicating increased pattern complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works demonstrated that FD varies according to the number of secondary divisions of the CNV: the higher the number of discernible secondary divisions, the higher the FD value. 11 , 12 Al-Sheik et al evaluated eyes with non-naïve active CNV and qualitative features of angiogenesis following one anti-VEGF IVI. They found attenuation and pruning of secondary ramifications in en-face OCTA, with subsequent reduction of the FD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations